Program One Day Boarding School Di Sekolah Muhammadiyah Dilihat Dari Prestasi Siswa: Program One Day Boarding School di Sekolah Muhammadiyah dilihat dari Prestasi Siswa - Fudlo, Nanik (Journal of Islamic and Muhammadiyah Studies, 2020)
This modern era of Islamic educational institutions in Indonesia at least begins with the Muhammadiyah movement as a public school plus and loving the Qur'an. In addi- tion to developing schools as "public schools plus loving the Qur'an", Muhammadiyah also developed a "Boarding School" (boarding school) which was initially criticized but continued to be developed eventually being accepted by the community, because it could answer the educational needs of the community. At present some Muhammadiyah schools that do not yet have boarding or boarding schools continue to develop Boarding Schools, with One Day Boarding Schools can improve student performance and also have a significant role to support the advancement of school programs. If the learning process is effective and efficient, it will increase students' interest in learning, so students will understand the material presented and have an impact on increasing student learn- ing achievement. It can be seen that various kinds of learning achievement are achieved in accordance with the vision and mission of the school, ranging from the development of Islamic values (Islamic Value Implementation), the formation of children's morals, life skill development, language development, development of academic achievement. The vision and mission achieved is in accordance with the institution that I examined, namely in MTs Muhammadiyah 1 Taman.